مدى فعالية استخدام مواقع التواصل الاجتماعي باعتبارها وسيطًا في العملية تعليمية - أ. انتصار ابوبكر الجماعي (Aljameai, 2026)
المستخلص:هدفت الدراسة إلى الكشف عن ظاهرة استخدام الطلاب مواقع التواصل الاجتماعي في التعليم ومساهمتها في رفع مستوى التحصيل العلمي، اعتمدت الدراسة على المنهج الوصفي أسلوب المسح، ولجمع البيانات تم تطبيق استمارة استبيان على عينة من طلبة كلية الإعلام والاتصال، جامعة اجدابيا واختيرت العينة العمدية، بلغ عددها(100) مفردة بحثية، وتوصلت الدراسة للعديد من النتائج أهمها: بينت الدراسة أن مواقع التواصل الاجتماعي" التيليجرام" يساهم في رفع المستوى العلمي لطلاب كلية الإعلام والاتصال، له فعالية بشكل كبير، وهذا ينعكس على المستوى العلمي على الطلاب بطريقة إيجابية، أتضح من خلال الدراسة أن أفراد عينة الدراسة يتفقون على وجود وصعوبات عند استخدام مجموعات التيليجرام في العملية التعليمية كصعوبات الحصول على المنهج المقرر من الأستاذ بصيغ إلكترونية.Abstract:The study aimed to reveal the phenomenon of students using social media in education and its contribution to raising the level of academic achievement. The study adopted the descriptive approach using the survey method. To collect data, a questionnaire was applied to a sample of students from the Faculty of Media and Communication, Ajdabiya University, and their number was (100). The purposive sample was chosen.The study reached several conclusions, most notably: The study showed that the social media platform "Telegram" is highly effective in raising the academic level of students in the Faculty of Media and Communication, and this is reflected positively in their academic performance. The study also revealed that the participants encountered drawbacks and difficulties when using Telegram groups in the educational process, such as the difficulty of obtaining the prescribed curriculum from the professor in electronic format.